PELATIHAN PENINGKATAN KESADARAN LITERASI KEUANGAN PADA GENERASI MILENIAL - Amran, Ellyana (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2025)
Financial literacy among the millennial generation remains relatively low, as they prioritize consumption over saving. This study aims to develop the financial behavior of vocational high school students in West Jakarta in terms of financial planning, self-control, and effective financial management. The method used in this study was a participatory approach, involving training, discussions, and simulations related to financial management. The study results indicate that participants’ understanding of financial planning implementation was pretty good. However, their understanding of self-control in managing finances was generally low, and similarly, their understanding of financial management implementation was also relatively low. The implications of these findings highlight the need for strong support to enhance financial literacy in the digital era among the millennial generation, particularly through guidance from parents, teachers, and community leaders, such as religious figures and youth leaders who can serve as role models.